1988
DOI: 10.1063/1.340981
|View full text |Cite
|
Sign up to set email alerts
|

TiAl3 formation by furnace annealing of Ti/Al bilayers and the effect of impurities

Abstract: Reactions of Ti/Al couples induced by furnace annealing were investigated (at elevated temperature) using large-grained Al substrates and vacuum-evaporated bilayers of both sequences. 4 He MeV backscattering spectrometry was principally used to monitor the reactions. Profiles of oxygen impurity were obtained by elastic 16 O(α,α)16 O resonant scattering. In the range of 460–515 °C, TiAl3 forms as a laterally uniform layer at the Ti/Al interface. The thickness of this compound layer increases as (annealing time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Similar behavior has been attributed to the formation of pores during the synthesis of various aluminides from powder mixtures [31][32][33][34][35][36]. This is also in agreement with studies suggesting that the diffusion of aluminum atoms into titanium particles is the predominant mechanism governing the formation of titanium aluminides [21,22,[25][26][27]. The globular morphology of the TiAl 3 phase obtained in this study is quite similar to what Xu et al [29] observed for the TiAl 3 phase in diffusion couple experiments.…”
Section: Tisupporting
confidence: 93%
See 1 more Smart Citation
“…Similar behavior has been attributed to the formation of pores during the synthesis of various aluminides from powder mixtures [31][32][33][34][35][36]. This is also in agreement with studies suggesting that the diffusion of aluminum atoms into titanium particles is the predominant mechanism governing the formation of titanium aluminides [21,22,[25][26][27]. The globular morphology of the TiAl 3 phase obtained in this study is quite similar to what Xu et al [29] observed for the TiAl 3 phase in diffusion couple experiments.…”
Section: Tisupporting
confidence: 93%
“…This observation has been explained on the basis of the higher diffusivity of aluminum ions in TiAl 3 in comparison with other aluminides, which in any case might be formed in small amounts [23]. Formation of TiAl 3 on the titanium side of the diffusion couple, together with the movement of markers, proved that aluminum is the dominant diffusing specie [4,21,22,[25][26][27]. However, diffusion of titanium has also been reported by some workers [28,29].…”
Section: Introductionmentioning
confidence: 58%
“…From Table 3, the Q k values of TiAl 2 and -TiAl phases formation in this study are very similar in magnitude with those of the TiAl 3 phase in the Ti-Al thin film diffusion systems, [9][10][11][12] but are lower than those of Ti-Al product formation in Ti-Al bulk systems. [6][7][8] A possible explanation in Q k for this discrepancy could be that the intrinsic defects, voids and the residual stress inherent in the thin film are more than those in the bulk form.…”
Section: Interreaction Kinetics Of Phase Formation Betweenmentioning
confidence: 50%
“…Moreover, from many reported diffusion couples tests in the Ti-Al system, the TiAl 3 layer is observed to grow rapidly and complies with the parabolic time dependence. 6,[9][10][11][12] In our cases, we suggest that the TiAl 3 growth in Fig. 1 is also following the parabolic law, although its growth kinetics is not investigated in this study.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation